2021
DOI: 10.1172/jci.insight.151551
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection of the pancreas promotes thrombofibrosis and is associated with new-onset diabetes

Abstract: SARS-CoV-2 infection of the pancreas promotes thrombo-fibrosis and is associated with new-onset diabetes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 35 publications
3
54
0
3
Order By: Relevance
“…Our TEM study results are confirmed by the results of previously published works, revealing the presence of coronavirus virions mainly in vascular endothelial cells of the lungs [63], intestines [64,65], kidneys [66], heart [67], skin [68], brain [69], liver [70], pancreas [71]. Furthermore, the TEM data confirms the hypothesis about the critical role of endothelial dysfunction in the development of multiorgan failure and the fatal outcome of COVID-19 [72,73].…”
Section: Discussionsupporting
confidence: 90%
“…Our TEM study results are confirmed by the results of previously published works, revealing the presence of coronavirus virions mainly in vascular endothelial cells of the lungs [63], intestines [64,65], kidneys [66], heart [67], skin [68], brain [69], liver [70], pancreas [71]. Furthermore, the TEM data confirms the hypothesis about the critical role of endothelial dysfunction in the development of multiorgan failure and the fatal outcome of COVID-19 [72,73].…”
Section: Discussionsupporting
confidence: 90%
“…Pancreas : In post-mortem material of COVID-19 patients, the viral N protein was detected in β-cells located in islets of the pancreas, which have been proposed as potential site of viral replication ( Müller et al, 2021 ; Qadir et al, 2021 ). This resulted in an impaired production of insulin upon stimulation with glucose in vitro and could be the reason for the hyperglycemia observed in COVID-19 patients ( Zhu L. et al, 2020 ; Affinati et al, 2021 ; Montefusco et al, 2021 ; Müller et al, 2021 ).…”
Section: Sars-cov-2mentioning
confidence: 99%
“…Immunohistochemistry and immunoblot staining patterns in human pancreas samples can vary depending on ACE2 antibody specificity [ 80 , 83 ]. Other explanations for the discrepancy of ACE2 expression levels in β cells have also been discussed, such as low sample size, results based on non-COVID-19 pancreatic tissues [ 75 , 81 , 82 , 83 , 84 ], low detection sensitivity of employed methods [ 85 , 89 ], differences in gender and ethnic background [ 81 , 85 , 86 ], inconsistent methodology for sample preservation or preparation between studies [ 75 ], negative effects of rapid pancreas autolysis for receptor detection [ 82 ], and rapid data evaluation and fast publication turnover [ 75 ]. While the expression of ACE2 on β cells is currently controversial and further research is needed, ACE2 expression in pancreatic ducts and in the microvasculature appears to be acknowledged by some study groups [ 75 ].…”
Section: Sars-cov-2 Receptors and Proteases In β Cellsmentioning
confidence: 99%
“…Reports describing the type of cells and tissues that are positive for SARS-CoV-2 protein or mRNA in the pancreas of infected individuals have been inconsistent. For instance, some reports indicate that SARS-CoV-2 protein/mRNA is specifically found in insulin-positive cells [ 48 ], ductal epithelium but not endocrine tissue [ 83 ]; however, other reports indicate that both endocrine and exocrine tissue are positive for them [ 81 , 84 , 85 , 86 ]. The discrepancies among these reports may be partly due to differences in expression levels of virus receptors between individuals, as well as due to differences in the employed methods for pancreatic hormone and viral-antigen co-staining.…”
Section: The Distribution Of Sars-cov-2 In the Pancreasmentioning
confidence: 99%